Perkembangan Muslim Champa: (Analisis Dari Penelitian Pemberitaan Muslim Cham Di Vietnam) - Ahmad Sayuti; Ade Irma; Zulkifli (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The ups and downs of the development of Islam in Vietnam is the background of this paper. Based on history, Islam has long been rooted in Vietnam, but until now Islam is still being adopted by the Vietnamese government. Therefore the author wants to examine how the development of Islam in Vietnam? The research method is qualitative with content analysis techniques on issues related to Vietnam circulating in online media portals and literature reviews (books, scientific journals). In 1986 the life of Muslims in Vietnam began to improve since the Socialist Government began constructing the Doi Moi (Renovation) policy which allowed Muslims to organize themselves in Vietnam, worship in surau, and madrasas were allowed to teach Islamic religion. But the fact is that there are still inconveniences in worship because the Vietnamese police are still secretly monitoring religious activities in places of worship (mosques), Islamic education and Islamic understanding are prohibited in public education, nor is it justified to establish religious schools. This condition shows that the freedom of Muslims in Vietnam is not intact. The convenience of worship, if it is still in an atmosphere of surveillance, will certainly make the Muslim community there afraid and a sense of mutual suspicion will arise, both among the community and between government officials. The Cham Muslim community is still having a hard time getting a job in their country, especially elite jobs or the private sector and government. The challenge of Muslims is a factor that influences the dynamics of Islamic development in Champa.